CO2 geo-storage capacity enhancement via nanofluid priming. (August 2017) - Al-Anssari, Sarmad; Arif, Muhammad; Wang, Shaobin; Barifcani, Ahmed; Lebedev, Maxim; Iglauer, Stefan
Graphical abstract: Abstract: CO2 geo-storage efficiency is strongly influenced by the wettability of the CO2 -brine-mineral system. With decreasing water-wetness, both, structural and residual trapping capacities are substantially reduced. This constitutes a serious limitation for CO2 storage particularly in oil-wet formations (which are CO2 -wet). To overcome this, we treated CO2 -wet calcite surfaces with nanofluids (nanoparticles dispersed in base fluid) and found that the systems turned strongly water-wet state, indicating a significant wettability alteration and thus a drastic improvement in storage potential. We thus conclude that CO2 storage capacity can be significantly enhanced by nanofluid priming.